Case report: secondary laparoscopic assissted transanal endorectal pull-through. A pre-eliminary study - Barmadisatrio, Barmadisatrio; Hariono, Hariono (Folia Medica Indonesiana, 2017)
The definitive treatment for Hirschsprung's disease is pullthrough procedure, that can be done through conventional pullthrough approach or through minimal invasive approach. The benefit of minimal invasive technique compared to conventinal open procedure is shorter time to oral intake, shorter length of stay, and less postoperative pain. Secondary LATEP is a minimal invasive pull through technique in patients with preexisting colostomy. Primary pullthrough sometimes cannot be done because limitation of health facilities, uneven distribution of pediatric surgeons throughout the country and late diagnosis of Hirschsprung's Disease. In dr Soetomo Hospital Surabaya, 7 secondary LATEP procedures were done in January to August 2014. The age range was 6 months to 8 years old. All patients survived, 1 patient had stenosis of anastomotic site 2 weeks postoperative, 3 had enterocolitis, 3 with no complication. Secondary LATEP is a minimal invasive approach for Hirschsprung's Disease that can be adjusted with Indonesia's social and economic condition, where most population was distant from an adequate health facility. As there is high incidence of malnutrition, enterocolitis and also the distance from appropriate health services, stoma formation is the first thing that can be done before definitive treatment.Secondary LATEP has never been done in Indonesia, and we still need more data and research to evaluate the benefit and disadvantage of this approach compared to conventional or minimal invasive primary pull through. In conclusion, secondary LATEP is an appropriate pullthrough alternative for Hirschsprung's Disease and applicable in Indonesia, considering the social and economy condition. Further study must be done to develop this method.